Digitalizing Rural Development in Indonesia: Unveiling Concepts and Strategies for Building Sustainable Digital Villages - Lucky Nugroho; Haura Hazimah Melzatia; Muhammad Izzat Abidin; Erik Nugraha; Safira (IAEI, 2023)
Digitalizing rural Indonesia can alter the quality of life and promote inclusive economic growth. This article discusses the importance of digital technology in rural areas, highlighting the impact of the Fourth Industrial Revolution and the COVID-19 epidemic on human behavior and the significance of ICT in modern communal life. The report emphasizes the necessity for reliable infrastructure, particularly internet networks and related technologies, to adopt ICT in rural areas. The qualitative study examines the urgency, characteristics, and growth methods of digital villages in Indonesia using current literature, official reports, and academic papers. A digital village development approach emphasizes interconnectedness, collaborative capacity building, digital integration benefits, and growth. The study examines Indonesia's digital village potential in farming, plantations, aquaculture, animal husbandry, travel, and hospitality. After examining the pros and cons of digital villages, the article emphasizes the need for a comprehensive program and policy to ensure rural digitization success. It offers practical solutions for using digital technology to overcome challenges and promote sustainable development in rural areas.